PENGARUH PEMASARAN RELASIONAL TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH DAN KEPERCAYAAN NASABAH TABUNGAN BANK BRI SYARIAH DI KOTA BANDA ACEH - Rizky Khaisar Maulana, Mukhlis Yunus (Departemen Manajemen, 2018)
Abstract: The purpose of the research is to know (1) relational marketing condition, customer satisfaction, customer trust, and customer loyalty, (2) influence of relational marketing influence to customer satisfaction, (3) influence of relational marketing to customer trust, (4) customer loyalty, (5) the influence of relational marketing on customer loyalty, (6) the influence of relational marketing on customer loyalty through customer trust and (7) indirect influence of relational marketing on customer loyalty through customer satisfaction and trust. This research was conducted at Bank BRI Syariah in Banda Aceh City, with research object related to relational marketing, customer loyalty, customer satisfaction and customer trust. The number of respondents in this study as many as 150 people with sampling technique done by non probability sampling. The results of research show that: relational marketing obtained average value of 3.52 or lower on scale 4 on the likert scale, customer satisfaction average value of 4.21, customer confidence average value of 4.26 and customer loyalty BRI Syariah bank in the City Banda Aceh average value of 3.60 has not run well because it has a lower value on a scale of 4 on units of Likert scale, because it obtained an average value of 3.5 on units Likert scale. Then relational marketing affects customer satisfaction, relational marketing affects customer's trust, relational marketing affects customer loyalty, relational marketing through customer satisfaction affect customer loyalty and relational marketing through customer trust affecting customer loyalty of Bank BRI Syariah in Banda Aceh CityKeywords Relational Marketing, Satisfaction, Trust and Customer Loyalty